Survey on Barriers to Critical Care and Palliative Care Integration. (February 2020) - Kyeremanteng, Kwadwo; Beckerleg, Weiwei; Wan, Cynthia; Vanderspank-Wright, Brandi; D'Egidio, Gianni; Sutherland, Stephanie; Hartwick, Michael; Gratton, Valérie; Sarti, Aimee J.
Purpose: It has been shown that integrating palliative care (PC) in intensive care unit (ICU) improves end-of-life care (EOLC), but very few Canadian hospitals have adopted this practice. Our study aims to evaluate the perceived quality of EOLC at participating institutions and explore barriers toward ICU-PC integration. Materials and Methods: A self-administered questionnaire was developed by a multidisciplinary team. Survey items were extracted from published quality indicators in EOLC and barriers to ICU-PC integration. The study took place at 2 academic institutions. Participants consisted of physicians and nurses, ICU administrators, and allied health workers. Results: An overall response of 45% was achieved. Of total, 85% of the respondents were ICU nurses. The following main themes were identified: (1) There is a poor presence of PC in the ICU and 78% of respondents felt that increasing ICU-PC integration will improve quality of EOLC; (2) the main barrier to integration was unrealistic patient and/or family expectations; and (3) criteria-triggered consultation to PC was the most feasible way to achieve integration. Conclusion: Our findings indicate that the majority of respondents perceive that the presence of PC in ICU will improve EOLC. Future quality improvement initiatives can focus on developing a set of criteria for triggering PC consults.